Peningkatan Pengetahuan APAR dan Alat Pemadam Api Tradisional pada Siswa SMAN 4 Surakarta - Jordan Syah Gustav; Nabylla Sharfina Sekar Nurriwanti; Rizqy Kartika Sari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Knowledge of fire extinguishers is crucial for enhancing preparedness in the event of a fire, particularly within school environments. This community service activity aims to analyze the knowledge of students at SMAN 4 Surakarta regarding portable fire extinguishers and traditional fire extinguishing tools through an educational approach. The method employed involved a pre-test and post-test design administered to 49 students who participated in a socialization session and a demonstration on the use of fire extinguishers. The results indicated a significant increase in students' knowledge concerning the use of both portable and traditional fire extinguishing tools. This activity not only improved students' understanding but also fostered awareness of the importance of preparedness and individual roles in fire prevention. Direct education combined with practical demonstrations proved to be an effective, engaging, and applicable learning medium. It is hoped that similar programs can be continuously implemented across all schools in Surakarta to cultivate a culture of safety awareness from an early age.